Student Team Achievement Division (STAD) and Cooperative Learning Model in Balaghah Learning - Nuryani Nuryani; Nurul Musyafaah; Baiq Tuhfatul Unsi; Muhammad Afthon Ulin Nuha (An Nabighoh, 2023)
This study aims to determine the effect of the Student Team Achievement Division (STAD) learning model on Balaghah subjects on student learning outcomes. This research is a type of quantitative research using an experimental model. The model used was a Quasi Experiment by applying a pre-test and post-test control group design involving two groups as research subjects at Madrasah Aliyah Bahrul Ulum Tambakberas Jombang class XI A as the control class and class XI B as the experimental class, each consisting of 30 students. The test uses multiple-choice questions designed according to indicators of learning outcomes. Data analysis techniques were used SPSS 25 with the t-test (Independent Sample T-Test). The results showed that the average value of the experimental class was higher than that of the control class. It is known that the average in the practical course is 80.7, while in the control class, it is 71.3, so there is a difference between the two. Based on the results of the t-test analysis (Independent Sample T-test) it resulted in Ho was rejected; thus, Ha was accepted, which suggests that the application of the STAD learning model is better than conventional learning on learning outcomes of class XI students of Madrasah Aliyah Bahrul Ulum Tambakberas Jombang.